Peran Guru Geografi dalam Membentuk Karakter Disiplin Siswa Melalui Pembelajaran di SMA Negeri 4 Palu - Adrian, Tri; Suyuti (Jurpis: Jurnal Pendidikan Ilmu Sosial, 2023)
This study aims to find out how the Role of the Geography Teacher is in Forming the Discipline Character of Students through Learning at SMA Negeri 4 Palu. The research approach used is a qualitative approach. This approach is a research strategy to obtain valid data according to the characteristics. The objects of research are school principals, geography teachers and students. Data collection techniques used in this study were carried out using observation, interviews and documentation approaches. While the data analysis method used is inductive analysis, meaning that the researcher describes specific events and then draws general conclusions. The results of the study show that geography teachers who always teach by giving advice and motivation do not forget to also reprimand and give educational punishments to students who break the rules. The role of the geography teacher is in shaping student discipline by providing guidance and motivation before entering class, applying discipline both in terms of time according to the rules that exist at school, dressing neatly, maintaining cleanliness so that you can study comfortably and have fun in class. Then in an effort there must be supporting and inhibiting factors. In practice teachers, parents, peers and the community environment can be factors that support or hinder efforts to build disciplinary character.